Recognizing Spam Zombies by Monitoring leaving Messages (International Journal of Engineering and Computer Science, 2013)
Compromised machines are one of the input security threats on the Internet; they are frequently used to launch various security attacks such as spamming and spreading malware, DDoS, and identity theft. Given that spamming provides a key economic incentive for attackers to recruit the large number of compromised machines, we focus on the detection of the compromised machines in a network that are involved in the spamming activities, commonly known as spam zombies. We develop an effective spam zombie detection system named SPOT by monitoring outgoing messages of a network. SPOT is designed based on a powerful statistical tool called Sequential Probability Ratio Test, which has bounded false positive and false negative error rates